2016
DOI: 10.1111/neup.12317
|View full text |Cite
|
Sign up to set email alerts
|

Adult‐onset atypical teratoid/rhabdoid tumor featuring long spindle cells with nuclear palisading and perivascular pseudorosettes

Abstract: Atypical teratoid/rhabdoid tumors (AT/RTs) are rare malignant neoplasms of the CNS that preferentially affect young children. We herein report an adult case of AT/RT surviving for more than 5 years with the residual tumor. The patient, a 24-year-old man at onset, presented with a contrast-enhancing mass lesion in the left occipital lobe, and underwent partial tumor resection. Histologically, the tumor was predominantly composed of long spindle cells exhibiting nuclear palisading and perivascular pseudorosettes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…From our systematic review, we found 50 adult patients who were diagnosed with AT/RT from the 39 articles included in this study (Table 1 ). The Supplementary Table 1 will include all the patients included in the pooled analysis ( 1 , 2 , 4 9 , 11 42 ). Of the 50 patients, the average age was 36.69 ( SD = 15.19) years with range from 18 to 59 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From our systematic review, we found 50 adult patients who were diagnosed with AT/RT from the 39 articles included in this study (Table 1 ). The Supplementary Table 1 will include all the patients included in the pooled analysis ( 1 , 2 , 4 9 , 11 42 ). Of the 50 patients, the average age was 36.69 ( SD = 15.19) years with range from 18 to 59 years.…”
Section: Resultsmentioning
confidence: 99%
“…Atypical teratoid/rhabdoid tumor (AT/RT) of the central nervous system is a highly malignant neoplasm ( 1 ). Although this tumor typically affects children younger than 3 years of age, it has been described in adults ( 1 , 2 ). Clinical presentation can vary depending on the patient's age, location and size of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] On the other hand, homozygous deletions occur in 20–25% of pediatric cases, but were only reported in 1/17 (6%) adult cases. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Atypical teratoid/rhabdoid tumour (AT/RT) is a malignant neoplasm representing less than 5% of central nervous system tumours [7,11]. Although this tumour is typically seen in the pediatric population, cases of AT/RT have been reported in adults [2].…”
Section: Introductionmentioning
confidence: 99%